Population dynamics of reindeer - Baskin, L. M. (Rangifer, 1990)
Five types of reindeer populations are distinguished in terms of population dynamics, population density, social structure and migration distance. Differences in the biological rhythms of the populations result in calving occuring 20 days before snow melting in all populations as well as maximal utilization by the deer of young green vegetation in summer. The growth of antlers may serve as a regulatior of biological rhytms. Populations differ in the level of social motivation. Formation of groups of not less than 30-35 animals ensures cooperative protection from insects and management of the group by man. The fidelity to the calving sites, summer ranges and constant migration routes is based on the common orientation reactions of the animals and social attraction. The direction and migration routes are detemined by obligate learning. The dynamics of populations depends on the fertility of 2 and 3 year old females which is determined by feeding conditions in summer and the activity of males during the rut. Migration plays an important role in the population dynamics.